Tracking the Money: The Case of 1MDB Scandal (Department of International Relations, Universitas Brawijaya, 2023)
The UN estimated US800 billion to US2 trillion is laundered every year. But unfortunately, about 90% of this amount remains undetectable to this day. This money laundering activity performs money laundering services on behalf of other people as their core business and is usually carried out in a different country. In this case, of course, money laundering becomes a complex transnational crime. This crime is widespread throughout the world, including in Malaysia. Malaysia is a country with an upper-middle-income economy that is very open to exposure to various threats of money laundering. According to Money Laundering Risk in 2022 data by the Basel Institute of Governance, Malaysia ranks 54th out of 128 countries with a score of 5.33 where a score of 10 indicates the highest risk. Even though Malaysia has the instruments to detect criminal acts, unfortunately, cooperation and political will are still considered lacking, making it difficult to eradicate it. This paper was compiled to identify money laundering in transnational crimes, and also to analyze the model of condition and model of operation in the 1MDB corruption case.